Social work and the law in scotland (Palgrave Macmillan, 2003)
This anthology offers a fresh and wide-ranging exploration of the critical links between practice issues and the legal framework regulating social work in Scotland. Made up largely of newly commissioned pieces by leading academics and practitioners in the field, it explores key conceptual and thematic issues and core areas of law and practice, as well as incorporating first-hand accounts from stakeholders in a range of settings.